Pressure Surges. Safe Design and Operation of Industrial Pipe Systems: 8th International Conference, Held in the Hague, the Netherlands on 12-14 April 2000 - Anderson A. (BHR Group Conference Series Pablication № 39)
It is important to avoid contamination of the environment or of the fluid being transported. Transient flow simulation and analysis is an essential requirement for assuring the safe operation of pipework systems. It has been shown to improve the availability and reliability of pipework with considerable savings in maintenance, repair, and liability costs. User-friendly software is available to assist engineers in many aspects of the field, but users should properly understand the physical process involved and the wide range of problems that can occur. They can then make informed interpretations of output. Without this know-how projects may proceed with a false sense of security and consequent risk. The papers included in Pressure Surges will deal with all aspects of unsteady flow and fluid transients in a variety of industries covering energy and power; oil and gas; chemical, process, and petrochemical; water supply; building services; utilities systems; and other industries.